Specification of Finite Element Model of Electronic Device using Modeldriven Wizard-based Guidance - Pavalkis, S.; Nemuraitė, L.; Tarvydas, P.; Noreika, A. (Elektronika ir Elektrotechnika, 2010)
When modeling the fields of electronic devices the emphasis is given to the improvement of intrinsic features of modeling process itself and continuous simplification of the model building stage. The latter problem is addressed by introducing the idea of wizardguided specifying the finite element model for electronic devices and generating code for them. Ill. 8, bibl. 9 (in English; summaries in English, Russian and Lithuanian).